Tinzaparin Provides Lower Lipid Profiles in Maintenance Hemodialysis Patients: A Cross-Sectional Observational Study. (12th November 2014) - Tsai, Ming-Hsien; Fang, Yu-Wei; Leu, Jyh-Gang
Abstract : As a low-molecular-weight heparin, tinzaparin has effectively been used as an anticoagulant during hemodialysis sessions. However, the impact of different heparin types on dyslipidemia is still controversial. In our study, 434 chronic hemodialysis patients were evaluated. The mean age was 65 ± 13. Forty-eight patients (11%) and 386 patients (89%) were in the tinzaparin and unfractionated heparin (UFH) groups, respectively. Triglyceride had significant difference between the two groups (P = 0.001 ) but total cholesterol, HDL, or LDL did not. In the univariate analysis, the triglyceride level was significantly associated with tinzaparin use [ β : −39.9, 95% confidence interval (CI): −76.7 to −3.0], and this association remained following the multivariate analysis ( β : −40.8, 95% CI: −75.1 to −6.5). The difference in serum total cholesterol level between tinzaparin and UFH became significant ( β : −13, 95% CI: −24.5 to −1.56) after adjustment in the multivariate analysis. Moreover, in a subgroup analysis, male diabetic patients showed lower serum triglyceride levels with the use of tinzaparin, while older, nondiabetic, male patients showed significant advantages in total cholesterol levels with the use of tinzaparin. Based on our findings, tinzaparin shows a significant association with a lower lipid profile in patients with chronic hemodialysis when compared to UFH.